PENILAIAN LIKUIFAKSI DENGAN PENGUJIAN TRIAKSIAL TERKONSOLIDASI-TAK TERDRAINASE - Upomo, Togani Cahyadi; Kusumawardani, Rini; Nugroho, Untoro; Kusbiantoro, Arief; Firdaus, Muh Arief; Syahputra, Muhammad Farhan (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
This study discusses the assessment of liquefaction by triaxial consolidated undrained (CU) testing. The soil sample employs Rembang silica sand with a grain size distribution that lies within the zone of liquefaction. In the test, Liquefaction develops in sand when the ratio of the change in pore water pressure to its confining stress (Ru) turns approximately 1 and the deviator stress drops to approximately zero. According to the findings, loose to medium-dense sand experience liquefaction when the applied confining stress is low (<100 kPa). In sandy soils, limited liquefaction occurs at confining pressures of 200 âˆ’ 400 kPa with the range of relative densities around 34.41% âˆ’ 47.78%. Critical state line develops from Triaxial CU testing to predict the undrained and drained behavior of sand.